2011
DOI: 10.1093/cid/cir831
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Vehicle for Transmission of Escherichia coli O157:H7 to Humans: Multistate Outbreak of E. coli O157:H7 Infections Associated With Consumption of Ready-to-Bake Commercial Prepackaged Cookie Dough--United States, 2009

Abstract: This is the first reported STEC outbreak associated with consuming ready-to-bake commercial prepackaged cookie dough. Despite instructions to bake brand A cookie dough before eating, case patients consumed the product uncooked. Manufacturers should consider formulating ready-to-bake commercial prepackaged cookie dough to be as safe as a ready-to-eat product. More effective consumer education about the risks of eating unbaked cookie dough is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…STEC-related disease outcomes can result in hemolytic-uremic syndrome (HUS) (7)(8)(9) followed by other complications (10-13) affecting various organs (9,12,(14)(15)(16)(17). STEC can be transmitted via foods (3,4,(18)(19)(20), water (21), animals (22)(23)(24)(25), and from person to person (26)(27)(28). Ruminants are natural carriers of STEC and are considered the main reservoirs for these pathogens (29).…”
mentioning
confidence: 99%
“…STEC-related disease outcomes can result in hemolytic-uremic syndrome (HUS) (7)(8)(9) followed by other complications (10-13) affecting various organs (9,12,(14)(15)(16)(17). STEC can be transmitted via foods (3,4,(18)(19)(20), water (21), animals (22)(23)(24)(25), and from person to person (26)(27)(28). Ruminants are natural carriers of STEC and are considered the main reservoirs for these pathogens (29).…”
mentioning
confidence: 99%
“…For example, participants discussed students' preparation and consumption of "convenience" foods as an important potential risk. The range of convenience foods available removes the need for developing basic cooking skills (Caraher and Lang, 1999), and outbreaks from convenience foods, including pre-made chicken quesadillas (Centers for Disease Control and Prevention (CDC), 2013) and cookie dough (Neil et al, 2012), have disproportionately impacted young people versus other ages. Thus, age-specific food safety education for high school students should teach them specifically how to safely prepare and consume these and other foods commonly consumed in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…A U.S. company initiated a voluntary recall of wheat flour and products contaminated with STEC O121 and O26 (CDC 2016). Neil et al (2012) reported STEC in uncooked cookie dough first, but could not trace back this contamination to flour unambiguously. These findings highlight the risk of pathogenic STEC in flour and flour products.…”
Section: Introductionmentioning
confidence: 97%
“…As wheat and rye flour is a stable food, the very high number of servings may pose a risk of ingesting undercooked flour. (Gilbert et al 2010;Neil et al 2012;Gieraltowski et al 2017;Wu et al 2017).…”
Section: Introductionmentioning
confidence: 99%